Não esqueça o melhor: tema e variações da sinfonia ética em O Princípio Esperança de Ernst Bloch - Lorenzoni, Anna Maria (2019)
Ernst Bloch has not written specific works on the subject of ethics. This, however, does not necessarily mean that his conception of the world has no fundamental ethical moti-vations, or that he has not wondered about the best ways of acting in the world. Indeed, in part of the literature devoted to author studies, especially that published in Brazil, there seems to be no doubt that his philosophy has an eminently ethical presupposition. There is, however, no unanimity about the content or the meaning of this ethic, which sometimes resembles moral imperatives, sometimes ways of life that claim to be un-derstanding. If indeed there is a Blochian ethic, how does it express itself, and what the-oretical elements support it? This thesis is an invitation to “listen to” the Principle of Hope, Bloch's great work, in order not only to explain the ethical coherence represented by the author's philosophy, but to argue that the ethical theme expresses the tonal center of his polyphony, although many times this theme is not as evident as other relevant themes that permeate the Blochian composition. In the following pages, we will weave a sym-phony of the Blochian ethics, seeking to identify its main melodic lines, the intensity of its movements, its density, the harmony between its parts, as well as the rhythm dedi-cated to each one. The Principle of Hope is the “libretto” that will guide our journey. Mix-ing sequences of fast and slow movements, the somewhat unusual Blochian symphony, as we intend to demonstrate, is divided into five movements, all devoted, in one way or another, to an admittedly central issue in Bloch’s work –the dreams of a better life, of a dignified and unexplored life. Repetitions, which do not occur casually in this symphony, always emerge on a new level, whose meanings approach but are not completely equal. “Do not forget the best of all”, but also “something is missing” and “stay awhile, you are so fair!” are variations of the same ethical theme, whose intensity of the performance varies according to its movements – sometimes an allegro, other times an adagio, sometimes a largo or even an andante. Its dynamics announce a crescendo, whose peak, however, never seems to find its summit, namely, the dwelling par excellence, the place of identity between human being and nature, the existential fulfillment.